If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6x + 2 + 7 = 5x + 5 + 7x Reorder the terms: 2 + 7 + 7x + 6x = 5x + 5 + 7x Combine like terms: 2 + 7 = 9 9 + 7x + 6x = 5x + 5 + 7x Combine like terms: 7x + 6x = 13x 9 + 13x = 5x + 5 + 7x Reorder the terms: 9 + 13x = 5 + 5x + 7x Combine like terms: 5x + 7x = 12x 9 + 13x = 5 + 12x Solving 9 + 13x = 5 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 9 + 13x + -12x = 5 + 12x + -12x Combine like terms: 13x + -12x = 1x 9 + 1x = 5 + 12x + -12x Combine like terms: 12x + -12x = 0 9 + 1x = 5 + 0 9 + 1x = 5 Add '-9' to each side of the equation. 9 + -9 + 1x = 5 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 5 + -9 1x = 5 + -9 Combine like terms: 5 + -9 = -4 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| -x+3=28 | | 16x+4(-31/4)=15 | | 3(4s-3)+4(3s+7)=139 | | Y^2+z^2=x^2 | | 4+-t-7=2+-3 | | 2x-15=-3x-22+5x | | 8/3x+1/3x=4x+33/3+8/3x | | 8=r+17 | | 9x-1=6x-58 | | (12x+5y)+(9y-11x)=0 | | 4a+7+2a-3= | | x^4-900=0 | | 16+4y=-15 | | (12x+5y)+(9y+11x)=0 | | x-7.1=-4.3 | | (12x+5y)(9y+11x)=0 | | 6(2q+3)+4(q-2)=122 | | r+1=4 | | t+9=4+2t | | 15x+10-8= | | 2(3x+1)=9x+1-3x+1 | | 1(x-7)-2(3x+5)=3 | | x^2+26x-57=0 | | (x^3/-2y^2)^3 | | -5n+6n+15-3n=-3n | | 8x-3=4x-63 | | 5(2v+7)+3(3v-4)=61 | | x^2+44x-300=0 | | -90=2b-2(-4b+5) | | 4(2x+1)(2x-9)=0 | | -3/5x=-15 | | 2p+5q=29 |